Estimation of Static Young Modulus for the Third section in Zubair Oil Field :A Comparison Study - Faraj, Ali K.; Abdul Hussein, Hassan A.; Jani, Ghassan H. (Journal of Petroleum Research and Studies, 2023)
A detailed analysis for the mechanical properties of the rock is necessary to maintain a well bore and avoid problems with well bore instability. Static young's modulus is one of the most crucial rock mechanical properties utilized in the drilling process to assess wellbore integrity and setting-up geomechanical earth model. Static young’s modulus change with varies of formation lithology’s which arise the critical need for estimation. The current study, a static young modulus values of different formations in section 12.25“in Zubair oil field are determined by depending on correlation to indicate variations in units and layers. Data of Gamma ray (GR), density log, sonic compression log (DTCO), and sonic shear log (DTSM) logs of well ZA-2 are utilized to estimate this attribute. Four different correlations that are set-up in Techlog 2015 software are used to achieve the aim of this study. These outcomes are calibrated using the fundamental laboratory tests (Brazilin and Triaxle test). The results showed that the modified Morales correlation provides a good matching with Calibration data, while four key data points are poorly correlated with the results of John Fuller's analysis.Also, Morales correlation shows unconformity when porosity reduced by less than 10% at different intervals, and Plumb Bradford correlation produces incorrect findings of static young’s higher than the dynamic. The results declare inversely relationship between porosity and young’s modulus.